(untitled) (Research, Society and Development, 2021)
A large part of the products generated from plastics is immediately discarded, little recycled and slowly decomposed, with Environmental Education standing out as a tool to raise awareness of the problems associated with these compounds. Therefore, this work aimed to encourage the knowledge of first year high school students to the safe use of plastic packaging and its risks associated with the environment and human health. As they are minors, participation requires a Term of Responsibility Signed by the students’ legal guardians. Initially, the students answered the questionnaire that sought to assess the context of Environmental Education in Basic Education in Uruçuí-PI, and the students’ knowledge of the theme. Subsequently, two meetings were held using the Google Meet tool, with debates relevant to the topic. After each meeting, a new questionnaire was administered out to estimate its influence on student learning. Use a Google Forms tool to create the forms and send them through the WhatsApp application. From the answers, we observed that Environmental Education was worked in an unsatisfactory and fragmented way in the school context of the participants, and those students know some problems associated with the use of plastic packaging, although they demonstrate ignorance of its human health risks and its greater consumption in the pandemic scenario. We also emphasize that it occurs when a remote form occurs if it has been tested and compared to the experienced period. We point out the need to discuss topics relevant to Environmental Education in a contextualized way to the student’s daily life and integrated with school content.